Characterization And Wear Performance Of Fabricated Alumina Based Cutting Tools - Mokhtar, Muhammad Faiz (2020)
Alumina (Al2O3) based cutting tool known to has a superior hardness and capable to cut metal in high speed machining without any present of coolant. However, this cutting tool possess brittleness that causes early chipping and breakage when engaged with workpiece material. The purpose of this research is to characterize the alumina, zirconia and alumina-zirconia mixture powder on the average particles size, surface area and microstructure. Then, to analyse the fabricated alumina and alumina-zirconia cutting tool based on dimension, density, hardness and flexural strength. Besides, to evaluate machining performance of alumina and alumina-zirconia cutting tools by varying cutting speeds and feed rates based on tool life. The process of fabricating Al2O3 and Zirconia Toughened Alumina (ZTA) cutting tool started with grinding and mixing of ceramic powder using ball mill. Especially for ZTA, the Al2O3 powder has been mixed with various ZrO2 content (5, 10, 15, 20 and 25 wt.%) before undergone ball mill. Then, Al2O3 and ZTA powders were compacted using cold isostatic press (CIP) before sintered at 1400oC for 9 hours to produce a solid insert cutting tool with specification of RNGN120600. The mechanical properties of each Al2O3 and ZTA cutting tool were evaluated based on density, hardness and fracture strength. The cutting tool that possess maximum hardness and flexural strength were selected for machining trials. The machining test was performed according to ISO 3685 with the cutting speeds of 200- 350 m/min, feed rates of 0.1-0.175 mm/rev and constant depth of cut of 0.5 mm of by using AISI 1045 medium carbon steel as workpiece. It was found that ZTA cutting tool that consisted of 80 wt.% Al2O3 and 20 wt.% ZrO2 recorded maximum density, hardness and fracture strength up to 96.51%, 70.1 HRC and 1449.3 MPa respectively. This value is much better than the Al2O3 sample which records the density, hardness and fracture strength of 84.89%, 43 HRC and 314.0 MPa respectively. In terms of wear performance, it was observed that the growth of flank wear for the Al2O3 cutting tool was more drastic than the ZTA cutting tool. Machining with ZTA cutting tool exhibited maximum tool life up to 224 s at a speed of 200 m/min and a feed rate of 0.125 mm/rev. Whereas the maximum life of the Al2O3 cutter is 151s at a speed of 200 m/min and a feed rate of 0.1 mm/rev. The ZTA cutting tool demonstrated gradual wear of abrasives, adhesives and built- up layers while Al2O3 was prone to breakage and flaking. On the analysis, it was found that the main factor affecting the good performance of ZTA cutting tool was the presence of ZrO2 particles in matrix Al2O3 which helps to control grain growth of Al2O3 while forming a compact and stronghold grain boundary. Thus, it enhanced the density, hardness, flexural strength and wear performance of ZTA cutting tool. The results provide a new knowledge on the effectiveness and capability of ceramic material which can be used as guidance if these ceramic materials should be expanded in other fields such as automotive, electrical and electronic.